Inefficient Investment Waves - He, Zhiguo; Kondor, Péter (Econometrica, 2016)
We propose a dynamic model of investment and trade in a market of a specialized technology subject to two main frictions. First, agents cannot raise outside capital. Second, a random group of agents will have the opportunity to invest in new technology and these opportunities are not contractible. The first friction implies the presence of invesment cycles with abundant invesment and low returns in booms and little invesment and high returns in recessions. Only when the second friction is present invesment cycles are constrained inefficient. Often the inefficiency is two-sided with too much invesment in booms and too little in recessions from a social point of view. Interventions targetting only the underinvesment in recessions might make all agents worse off. Also, the two-sided inefficiency typically implies too volatile prices and too frequent realizations of abnormally low prices compared to fundamentals.